Pregnant and postpartum women's experiences of weight stigma in healthcare - Angela C. Incollingo Rodriguez; Stephanie M. Smieszek; Kathryn E. Nippert; A. Janet Tomiyama (BMC, 2020)
Abstract Background Weight stigma is a societal phenomenon that is very prevalent in healthcare, precipitating poor patient-provider relationships, discontinuity of care, and delayed cancer screening. Little research, though, has investigated weight stigma in prenatal and postpartum healthcare. To address this gap, this study examined the prevalence and frequency of weight-stigmatizing experiences in prenatal and postpartum healthcare. Methods 501 pregnant and postpartum women responded to an online survey where they reported whether they had experienced weight stigma in prenatal or postpartum healthcare and, if so, how frequently. Participants also responded to questions about how providers had treated them regarding their weight and their reactions to these experiences. A subset of participants (n = 80) also provided examples of their experiences, and these were subjected to a thematic analysis and coded for overarching themes. Results Nearly 1 in 5 women (n = 92) reported experiencing weight stigma in healthcare settings. Percentages differed by BMI, with 28.4% of participants with pre-pregnancy obesity endorsing healthcare providers as a source of weight stigma. Experiences occurred between "less than once a month" and "a few times a month." Obstetricians were the most commonly-reported source (33.8%), followed by nurses (11.3%). Participants reported feeling judged, shamed, and guilty because of their weight during healthcare visits. Additionally, 37 participants (7.7%) reported having changed providers because of treatment regarding their weight. Many also reported that they expected to feel or had felt uncomfortable seeking help with breastfeeding from a healthcare professional. Finally, thematic analysis of the open-ended examples identified four key themes: (1) negative attitudes and unkind or disrespectful treatment from providers; (2) evaluative comments about their weight; (3) healthcare providers focusing on their high-risk status and potential negative consequences (often when birth outcomes were ultimately healthy); and (4) inappropriate or demeaning comments. Conclusions Weight stigma may be a common experience in pregnancy and postpartum healthcare. Providers need additional training to avoid stigmatizing their patients and inadvertently undermining patient-provider relationships, quality of care, and health outcomes.